Morphological effect of cerulenin treatment on Streptococcus faecalis as studied by ultrastructure reconstruction. - Higgins, M L (1980)
Exponential-phase cells of Streptococcus faecalis ATCC 9790 were treated with a concentration of cerulenin (5 micrograms/ml) that has been shown to block both lipoteichoic acid and lipid synthesis and cell division within 10 min. The morphological effect of this treatment was studied by making three-dimensional reconstructions of cells based on measurements taken from axial thin sections. This analysis indicated that cerulenin interferes with cell division by inhibiting normal constriction of the division furrow and centripetal growth of the cross wall in envelope growth sites. Rather than dividing, many of the sites in treated cells apparently continue to elongate and produce abnormally large amounts of peripheral wall surface. These observations were interpreted in terms of a previously proposed model in which cerulenin would prevent the synthesis of a lipid-containing inhibitor of autolytic enzyme activity needed for division. In addition, measurements showed that the average number of envelope growth sites per cell increased during treatment, suggesting that although cerulenin treatment blocks division, it does not interfere with the formation of new envelope growth sites. It was also observed that the size and frequency of mesosomes did not decline during the 60-min period of drug treatment. This tends to decrease the likelihood that mesosomes are formed from a pool of intracellular membrane precursors that would be depleted during a period of restricted lipid biosynthesis.